Therapeutic Potential of a Scorpion Venom-Derived Antimicrobial Peptide and Its Homologs Against Antibiotic-Resistant Gram-Positive Bacteria - Liu, Gaomin; Yang, Fan; Li, Fangfang; Li, Zhongjie; Lang, Yange; Shen, Bingzheng; Wu, Yingliang; Li, Wenxin; Harrison, Patrick L.; Strong, Peter N.; Xie, Yingqiu; Miller, Keith; et al. (Frontiers in Microbiology, 2018)
The alarming rise in the prevalence of antibiotic resistance among pathogenic bacteria poses a unique challenge for the development of effective therapeutic agents. Antimicrobial peptides (AMPs) have attracted a great deal of attention as a possible solution to the increasing problem of antibiotic-resistant bacteria. Marcin-18 was identified from the scorpion Mesobuthus martensii at both DNA and protein levels. The genomic sequence revealed that the marcin-18 coding gene contains a phase-I intron with a GT-AG splice junction located in the DNA region encoding the N-terminal part of signal peptide. The peptide marcin-18 was also isolated from scorpion venom. A protein sequence homology search revealed that marcin-18 shares extremely high sequence identity to the AMPs meucin-18 and megicin-18. In vitro, chemically synthetic marcin-18 and its homologs (meucin-18 and megicin-18) showed highly potent inhibitory activity against Gram-positive bacteria, including some clinical antibiotic-resistant strains. Importantly, in a mouse acute peritonitis model, these peptides significantly decreased the bacterial load in ascites and rescued nearly all mice heavily infected with clinical methicillin-resistant Staphylococcus aureus (MRSA) from lethal bacteremia. Peptides exerted antimicrobial activity via a bactericidal mechanism and killed bacteria through membrane disruption. Taken together, marcin-18 and its homologs have potential for development as therapeutic agents for treating antibiotic-resistant, Gram-positive bacterial infections.